Possible effects of the Common Fund - Joachim Betz (Intereconomics, 1979)
After five years of tough negotiations at numerous conferences about an integrated Programme for Commodities (IPC) the participating countries agreed in March 1979 on basic and operational regulations for the key instrument of this programme, a Common Fund. In its present version it is closely related to the ideas of the “hard-liners” among the industrialized states and—what is most important—seems incapable of contributing significantly to a solution of the global investment, diversification and price stabilization problems in the commodity sector.
Keywords: 330; Raw Materials